Low grade intraepithelial lesion (LSIL) in cervical epithelium H&E stain and AgNOR stain - Faisal, Ghasak Ghazi (2020)
2 microscopic views of cervical epithelium showing low grade intraepithelial lesion LSIL stained with hematoxilin and eosin and AgNOR stain